2022
DOI: 10.1108/srj-07-2021-0257
|View full text |Cite
|
Sign up to set email alerts
|

Does source credibility matter in promoting sustainable consumption? Developing an integrated model

Abstract: Purpose This paper aims to explore the role of source credibility while purchasing environment-friendly products using Ajzen’s (1991) theory of planned behavior as underpinning model. Design/methodology/approach The proposed theoretical model was empirically tested with the data collected from 334 respondents using structural equation modeling. Findings The results gave empirical support to the addition of source credibility to the original theory of planned. Moreover, consumer attitude was found mediating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 179 publications
(317 reference statements)
1
4
0
Order By: Relevance
“…Therefore, an individual's perceived control over their behavior indicates whether they will be inclined towards buying green products or not. These results are consistent with many previous studies that have reported attitude and perceived behavioral control as the main determinants of sustainable consumption behavior [14][15][16]. Several studies conducted in the domain of sustainable consumption have reported subjective norms to have either a reduced impact or no impact on purchase intention [18,19,33,43].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, an individual's perceived control over their behavior indicates whether they will be inclined towards buying green products or not. These results are consistent with many previous studies that have reported attitude and perceived behavioral control as the main determinants of sustainable consumption behavior [14][15][16]. Several studies conducted in the domain of sustainable consumption have reported subjective norms to have either a reduced impact or no impact on purchase intention [18,19,33,43].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it has become important to investigate the major determinants of green purchase behavior. Ajzen's [13] "Theory of planned behavior" (or TPB model) is a very popular theoretical model and has frequently been used to predict an individual's purchase behavior, including green purchase behavior [12][13][14][15][16][17][18][19]. However, green consumption has been reported to be influenced by a number of sociocultural, demographic, and psychological factors [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Underpinning Theory: According to the theory of reasoned action (Fishbein and Ajzen, 1975), an individual's intention to engage in a particular behavior is formed by their attitude towards the behavior and the subjective norm (their beliefs about what they should do and how important other people's opinions are to them), and this intention then tends to perform the behavior. Social psychologists believe that the key to understanding a person's behavior is their attitude (Kumar et al, 2023). However, it is a difficult effort to understand the relationship between attitude and behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green skincare products are formulated from botanically sourced ingredients and contain natural carrier agents; they are free of synthetic chemicals that are beneficial to the skin [ 10 ]. However, due to the overstated claims in advertisements, consumers are being found to be sensitive to green products [ 11 ]. Concurrently, despite the growing significance of green products, the adoption of green skincare products has yet to be thoroughly researched.…”
Section: Introductionmentioning
confidence: 99%